ANALISIS KONFLIK TOKOH UTAMA DALAM NOVEL REVERED BACK KARYA INGGRID SONYA - Falah, Utin Amanda Chandrika; Seli, Sesilia; Heryana, Nanang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThis research describes internal conflicts and eksternal conflicts in Inggrid Sonya"™s Revered Back novel which is then used as teching material in the preparation of learning plans using the Revered Back novel teks. This research uses a descriptive method with qualitative research form. This study uses a literary psychology approach. The data source in this research is the novel Revered Back by Inggrid Sonya and the research data is in the form of internal conflict and external conflict in the form of words, phrases or sentences contained in the novel. Using documentary study data collection techniques and data cards as data collection tools. The technique of testing the validity of the data was carried out by observing persistence, triangulation, and referential adequacy. The first research results: internal conflicts of the main character, namely events that can cause feelings of sadness, hatred, depression, confusion, disappointment, hurt, and regret. Second: external conflict of the main character, namely conflict that occurs because of physical clashes between characters and arguments. Third: The Learning Implementation Plan (RPP) has been successfully prepared to teach basic competence 3.9 and basic competence 4.9 in class XII SMA, using the novel Revered Back by Inggrid Sonya.Keywords: Analysis, Conflict, Main Character Conflict, Novel